2003
DOI: 10.1007/s00122-003-1423-9
|View full text |Cite
|
Sign up to set email alerts
|

Generation and flanking sequence analysis of a rice T-DNA tagged population

Abstract: Insertional mutagenesis provides a rapid way to clone a mutated gene. Transfer DNA (T-DNA) of Agrobacterium tumefaciens has been proven to be a successful tool for gene discovery in Arabidopsis and rice ( Oryza sativa L. ssp. japonica). Here, we report the generation of 5,200 independent T-DNA tagged rice lines. The T-DNA insertion pattern in the rice genome was investigated, and an initial database was constructed based on T-DNA flanking sequences amplified from randomly selected T-DNA tagged rice lines using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 49 publications
4
55
0
1
Order By: Relevance
“…For this reason, transgenes may be inserted in functional genomic regions, disrupting the structure and/or altering the regulation patterns of genes from the plant host genome. Results obtained from largescale T-DNA tagging experiments in Arabidopsis thaliana (Szabados et al 2002;Alonso et al 2003;Forsbach et al 2003;Qin et al 2003) and Oryza sativa (Jeong et al 2002(Jeong et al , 2006Chen et al 2003;Sha et al 2004;Zhang et al 2007) showed a non-random distribution of T-DNA insertion sites, more frequent in genic sequences endowed with different functions such as metabolism, signal transduction and transcription, disease processes and defence mechanisms, intracellular traffic. Experiments in other organisms, namely the legume Medicago truncatula (Scholte et al 2002), barley (Salvo-Garrido et al 2004, potato and tobacco (Koncz et al 1989;Lindsey et al 1993) also suggested that T-DNA insertion occurred generally into coding sequences.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, transgenes may be inserted in functional genomic regions, disrupting the structure and/or altering the regulation patterns of genes from the plant host genome. Results obtained from largescale T-DNA tagging experiments in Arabidopsis thaliana (Szabados et al 2002;Alonso et al 2003;Forsbach et al 2003;Qin et al 2003) and Oryza sativa (Jeong et al 2002(Jeong et al , 2006Chen et al 2003;Sha et al 2004;Zhang et al 2007) showed a non-random distribution of T-DNA insertion sites, more frequent in genic sequences endowed with different functions such as metabolism, signal transduction and transcription, disease processes and defence mechanisms, intracellular traffic. Experiments in other organisms, namely the legume Medicago truncatula (Scholte et al 2002), barley (Salvo-Garrido et al 2004, potato and tobacco (Koncz et al 1989;Lindsey et al 1993) also suggested that T-DNA insertion occurred generally into coding sequences.…”
Section: Introductionmentioning
confidence: 99%
“…The promise of this technology as illustrated by the cloning and characterization of several genes in Arabidopsis and the world wide efforts in progress should enable coverage of this model genome in a few years to come. Interestingly, T-DNA mutational approach is now being successfully modified to tag genes in a number of economically important plant species, rice (430 Mbp) (Hiroyuki et al 1999;Kolesnik et al 2004;Sha et al 2004), tomato (953 Mb) (Meissner et al 2000), Brassica napus (1182 Mbp) (Bade et al 2003), Medicago truncatula (~454 to 526 Mbp) (Trieu et al 2000) and poplar (550 Mbp America, March 2000, vol. 97, no.…”
Section: Discussionmentioning
confidence: 99%
“…T-DNA tagging has been used successfully for gene discovery in rice. An initial database has also been constructed using T-DNA flanking sequences (Sha et al 2004). T-DNA tags have also been observed to insert preferentially into gene rich regions Sha et al 2004).…”
Section: Insertional Mutagenesis In Other Angiospermsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the T-DNA distribution was positively correlated with expressed genes but negatively with transposable elements and small RNAs. Indeed, it has been suggested that the positive correlation between expressed genes and T-DNA insertions may be due to the "open" state of actively transcribed regions, rendering the DNA in these regions more accessible [58,60,61]. The negative correlation with small RNAs suggests that small RNAs also play roles in influencing T-DNA integration by maintaining the DNA in a condensed state.…”
Section: Distribution Of T-dna Insertions On Chromosomesmentioning
confidence: 99%